Zboża Bizancjum. Kilka uwag na temat roli produktów zbożowych na podstawie źródeł greckich - Kokoszko, Maciej; Jagusiak, Krzysztof (Zeszyty Wiejskie, 2012)
The present article researches into the wide variety of cereal products available on the market of Byzantium, and especially in its capital, namely the city Constantinople, in the late antique and early Byzantine period. The authors try to outline the most popular cereal foods (concentrating on wheat and barley products) and establish their dietetic evaluation present in the writings of Galen, Oribasius, Aetius of Amida, Anthimus and others dieticians who formulated doctrines accepted in Byzantium. They also make use of dietetic treatises to retrieve basic information on the culinary art of the period between the IVth and VIIth centuries.